2021
DOI: 10.1016/j.isci.2021.102498
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial CMPK2 mediates immunomodulatory and antiviral activities through IFN-dependent and IFN-independent pathways

Abstract: Summary Mitochondria regulate the immune response after dengue virus (DENV) infection. Microarray analysis of genes identified the upregulation of mitochondrial cytidine/uridine monophosphate kinase 2 (CMPK2) by DENV infection. We used small interfering RNA-mediated knockdown (KD) and CRISPR-Cas9 knockout (KO) approaches, to investigate the role of CMPK2 in mouse and human cells. The results showed that CMPK2 was critical in DENV-induced antiviral cytokine release and mitochondrial oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…In the current report, we first demonstrated that chCMPK2 inhibited the propagation of AIV H9N2 in a dose-dependent way, and chCMPK2 may also be an antiviral molecule against NDV. CMPK2 has been reported to be able to inhibit viral and bacterial infection, including SVCV, Dengue virus (DENV), Duck Tembusu virus (DTMUV), HIV-1 and Aeromonas hydrophila CCL1 ( El-Diwany et al, 2018 ; Liu et al, 2019 ; Xiang et al, 2020 ; Feng et al, 2021 ; Lai et al, 2021 ). Our analysis indicated that overexpression of chCMPK2 in DF-1 cells significantly inhibited H9N2 NP expression at the mRNA and protein levels, and knockdown of chCMPK2 had the opposite effects, which suggested that chCMPK2 was an important antiviral factor against AIV.…”
Section: Discussionmentioning
confidence: 99%
“…In the current report, we first demonstrated that chCMPK2 inhibited the propagation of AIV H9N2 in a dose-dependent way, and chCMPK2 may also be an antiviral molecule against NDV. CMPK2 has been reported to be able to inhibit viral and bacterial infection, including SVCV, Dengue virus (DENV), Duck Tembusu virus (DTMUV), HIV-1 and Aeromonas hydrophila CCL1 ( El-Diwany et al, 2018 ; Liu et al, 2019 ; Xiang et al, 2020 ; Feng et al, 2021 ; Lai et al, 2021 ). Our analysis indicated that overexpression of chCMPK2 in DF-1 cells significantly inhibited H9N2 NP expression at the mRNA and protein levels, and knockdown of chCMPK2 had the opposite effects, which suggested that chCMPK2 was an important antiviral factor against AIV.…”
Section: Discussionmentioning
confidence: 99%
“…CMPK2 played a critical role in dengue virus (DENV)-induced mitochondrial oxidative stress, cytokine release, and mitochondrial DNA (mtDNA) release to the cytosol. CMPK2 depletion could suppress the DENV-induced cell migration, TLR9 activation, and inflammasome pathway, and the increasing viral production ( 19 ). CMPK2 mediated the antiviral activity ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMPK2 depletion could suppress the DENV-induced cell migration, TLR9 activation, and inflammasome pathway, and the increasing viral production ( 19 ). CMPK2 mediated the antiviral activity ( 19 ). In the present study, CMPK2 was obviously up-regulated in chicken jejuna from LPC-treated groups which agree with the report that CMPK2 was involved in mtDNA synthesis and antiviral immunity in animals ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CMPK2, studies using murine genital tract epithelial cells have also shown an upregulation of CMPK2 mRNA upon C. muridarum infection [60]. The enzyme CMPK2 not only supplies deoxyribonucleotides for the synthesis of mitochondrial DNA (mtDNA) [61] but it also possesses immunomodulatory and antiviral activities: CMPK2 was shown to limit dengue virus infection of murine and human cells in an IFN-dependent and IFN-independent manner [62]. Taken together, the Ct-induced upregulation of interferon regulated genes in pOECs potentially not only limits Ct propagation within the infected cell, but it could also promote immunomodulation in the genital tract.…”
Section: Innate Immune Response Of Porcine Oviduct Epithelial Cells To Chlamydia Trachomatis Infectionmentioning
confidence: 99%